African American women writers' historical fiction - Nunes, Ana (Palgrave Macmillan, 2011)
This volume explores African American historical fiction written by women in the last four decades of the twentieth century. Nunes' approach to the texts aims at emphasizing the narrative and thematic achievements of individual novels set in the context of the main trends and developments of the contemporary African American historical novel.